A rare case of non-clostridial infection in a non-diabetic patient. Issue 1 (8th January 2020) - Darat, Helin Nie; Kanodia, Avinash Kumar; Yong, Aiwain; Ram, Bhaskar
Abstract : A 76-year-old man presented with neck swelling associated with pain and fever. On examination, there was a submental neck swelling. His initial CT scan showed multiloculated abscess centred in the left submandibular gland. He remained febrile despite on intravenous ceftriaxone and metronidazole. A repeat CT scan revealed significant worsening with multiple pockets of fluids with gas locules in the deep neck spaces. He subsequently underwent neck exploration and drainage of neck abscess. Extensive necrotic tissue was found intraoperatively and thick pus was drained from the bilateral parapharyngeal, submental spaces and anterior mediastium. Pus culture profusely grew of Eggerthella species. Patient recovered well following further intravenous antibiotic therapy. Diabetes mellitus and odontogenic infections are the common risk factors in deep neck infections. Our patient is however non-diabetic and edentulous. Current case is presented to serve as a rare case of neck abscess with unusual cause in a non-diabetic patient.